2023
DOI: 10.1038/s41398-023-02607-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of polygenic risk for bipolar disorder with grey matter structure and white matter integrity in youth

Xinyue Jiang,
Clement C. Zai,
Kody G. Kennedy
et al.

Abstract: There is a gap in knowledge regarding the polygenic underpinnings of brain anomalies observed in youth bipolar disorder (BD). This study examined the association of a polygenic risk score for BD (BD-PRS) with grey matter structure and white matter integrity in youth with and without BD. 113 participants were included in the analyses, including 78 participants with both T1-weighted and diffusion-weighted MRI images, 32 participants with T1-weighted images only, and 3 participants with diffusion-weighted images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
1
3
0
Order By: Relevance
“…The results showed that BD-PRS is negatively correlated with gray matter structure and fractional anisotropy (FA) in regions associated with BD in adolescents. 30 These research findings support the feasibility of BD-PRS as a neuroimaging marker for BD. Future longitudinal studies are needed to examine whether BD-PRS can predict neurodevelopmental changes between BD and healthy controls (HC), as well as its interaction with the course of illness and long-term medication use.…”
Section: The Phenotype Of Bd Based On Prssupporting
confidence: 60%
“…The results showed that BD-PRS is negatively correlated with gray matter structure and fractional anisotropy (FA) in regions associated with BD in adolescents. 30 These research findings support the feasibility of BD-PRS as a neuroimaging marker for BD. Future longitudinal studies are needed to examine whether BD-PRS can predict neurodevelopmental changes between BD and healthy controls (HC), as well as its interaction with the course of illness and long-term medication use.…”
Section: The Phenotype Of Bd Based On Prssupporting
confidence: 60%
“…The debate surrounds the suitability of genome-wide PRS as a genetic tool for investigating psychiatric disorders [ 93 ]. While it enhances generalizability by capturing a broad range of common genetic factors for BD [ 55 ], its inclusion of alleles with potentially diverse associations with brain structure may mask effects of specific gene sets [ 93 ]. This debate is reflected in conflicting findings: On the one hand, there are studies failing to establish significant associations between BD or SZ PRS and brain structure [ 35 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This debate is reflected in conflicting findings: On the one hand, there are studies failing to establish significant associations between BD or SZ PRS and brain structure [ 35 , 93 ]. In contrast, a recent study in bipolar adolescents, benefiting from fewer confounding factors such as illness course or medication, demonstrated higher bipolar PRS scores correlating with both GM structure and WM diffusion [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation